2001
DOI: 10.14411/fp.2001.015
|View full text |Cite
|
Sign up to set email alerts
|

New thiadiazine derivatives with activity against Trypanosoma cruzi amastigotes

Abstract: Abstract. The cytotoxicity of 18 new 1,2,6-thiadiazin-3,5-dione 1,1-dioxides was evaluated. This group of products was previously assayed against epimastigotes of Trypanosoma cruzi and some of them showed a high antiprotozoal activity. Thereafter 13 compounds with a high anti-epimastigote activity and low cytotoxicity were selected to be assayed against amastigotes. Some of the products showed the same or even lower cytotoxicity than nifurtimox and benznidazole, but most of them were very toxic for macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…Among the less cytotoxic derivatives of the second series, one compound showed activity against intracellular amastigotes similar to the standard drug (Muelas et al 2001).…”
Section: Synthetic Drugsmentioning
confidence: 96%
“…Among the less cytotoxic derivatives of the second series, one compound showed activity against intracellular amastigotes similar to the standard drug (Muelas et al 2001).…”
Section: Synthetic Drugsmentioning
confidence: 96%
“…The cells were allowed to attach for 24 h at 37°C in atmosphere with 5% CO 2 in air, and then exposed to the extracts for another 24 h. Afterwards, cytotoxicity was determined by addition of MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazlium bromide] as previously (Muelas et al, 2001).…”
Section: Cytotoxicity To Macrophagesmentioning
confidence: 99%
“…In this way, new 5-nitro-2-furyl derivatives have been synthesized [6][7][8][9][10]. Previously, were reported the anti-Trypanosoma cruzi properties in vitro and in vivo of some of these derivatives [11,12]. It was also demonstrated that the presence of a nitro moiety, as a source of free radicals, seems to be a feature that increases the anti-T. cruzi activity [13].…”
Section: Introductionmentioning
confidence: 99%